Advancing the Role of Food Processing for Improved Integration in Sustainable Food Chains - Knorr, Dietrich; Augustin, Mary Ann; Tiwari, Brijesh (Frontiers in Nutrition, 2020)
Food scientists need to work together with agriculturists, nutritionists, civil society and governments to develop an integrative approach to feed a growing population sustainably. Current attention on food sustainability mainly concentrates on production agriculture and on nutrition, health and well-being. Food processing, the necessary conversion of raw materials to edible, functional and culturally acceptable food products, is an important link between production and consumption within the food value chain Without increased attention to the role of food processing for a maintainable food supply, we are unlikely to succeed in addressing the mounting challenges in delivering sustainable diets for all people. The objective is to draw on multidisciplinary insights to demonstrate why food processing is integral to a future food supply. We aim to exemplify the importance of essential relevant sustainability indicators and impact assessment for developing informed strategies to feed the world within planetary boundaries. We provide a brief outlook on sustainable food sources, review food processing and future directions. We highlight the challenges and suggest strategies for improving the sustainability of food systems, to hopefully provide a catalyst for considering implementable initiatives for improving food and nutrition.